Inner bark as a crucial tissue for non-structural carbohydrate storage across three tropical woody plant communities - Rosell, Julieta A.; Piper, Frida I.; Jiménez-Vera, Cipatli; Vergílio, Paula C. B. [UNESP]; Marcati, Carmen R. [UNESP]; Castorena, Matiss; Olson, Mark E. (Wiley, 2021)
Non-structural carbohydrates (NSC) are crucial for forest resilience, but little is known regarding the role of bark in NSC storage. However, bark's abundance in woody stems and its large living fraction make it potentially key for NSC storage. We quantified total NSC, soluble sugar (SS) and starch concentrations in the most living region of bark (inner bark, IB), and sapwood of twigs, trunks and roots of 45 woody species from three contrasting tropical climates spanning global extremes of bark diversity and wide phylogenetic diversity. NSC concentrations were similar (total NSC, starch) or higher (SS) in IB than wood, with concentrations co-varying strongly. NSC concentrations varied widely across organs and species within communities and were not significantly affected by climate, leaf habit or the presence of photosynthetic bark. Starch concentration tended to increase with density, but only in wood. IB contributed substantially to NSC storage, accounting for 17–36% of total NSC, 23–47% of SS and 15–33% of starch pools. Further examination of the drivers of variation in IB NSC concentration, and taking into account the substantial contribution of IB to NSC pools, will be crucial to understand the role of storage in plant environmental adaptation.
Keywords: bark photosynthesis; bark thickness; non-structural carbohydrate pools; root storage; secondary phloem; soluble sugars; starch; wood density; wood storage